GERMANY 1945 VIEWS OF WAR AND VIOLENCE - Barnouw, Dagmar (Indiana University Press, 1996)
Photographers from the U.S. Army's Signal Corps were with the troops that drove back Hitler's troops and occupied Germany at the end of WWII. Soon photos of death camps and starving POWs shocked the home front, providing ample evidence of Nazi brutality. Yet did the faces of the defeated Germans show remorse? The victors saw only arrogance, servility, and the resentment of a population thoroughly brainwashed by the Nazis. In fact, argues Dagmar Barnouw, the photographs from this period tell a more complex story and hold many clues for a better understanding of the recent German past.